Trainee or replacement teachers’ perceptions towards the implementation of school based assessment in lower secondary schools / Mohd Hasrul Othman - Othman, Mohd Hasrul (Faculty of Education, 2013)
Since year 2011, our educational system had shifted its attention to a less examination centred system which is now called school-based assessment (SBA). This system is not new to the world but new to Malaysia. There are various research had been done regarding this new system which some support and others opposed it. Henceforth, it is desirable to find out trainee or replacement teachers’ perceptions towards the implementation of school-based assessment in lower secondary schools. Trainee or replacement teachers usually are neglected because they are not permanent teachers. However, their opinion and ideas regarding should not be treated the same. This exploratory study aimed to investigate trainee or replacement teachers’ perceptions towards the implementation of school-based assessment in lower secondary school students. This exploratory study was developed by 3 research objectives and 3 research questions intended to fulfil the aim of this exploratory study. The respondents for this exploratory study consisted of 29 trainee teachers and 1 replacement teacher. This exploratory study used both quantitative and qualitative methods in order to answer the research questions outlined in this exploratory study. The findings showed that most respondents were not properly introduced to the system in which mostly influenced their responses in this study. Secondly, most of the respondents only agreed with the concept of school-based assessment (SBA) but not how it is implemented. Thirdly, their methods of implementing SBA mostly did not have much different compared to how they teach in normal class. The only problems come from their lack of skills and knowledge in assessing students’ performance despite they had more free time compared to the existing teachers. Lastly, respondents also had suggested few strategies needed to improve the implementation of this system. In conclusion, based on this study it showed that these groups of educators’ opinions, roles and functions should not be discarded when new policy been implemented because they are also teachers at school.